2014
DOI: 10.1016/j.taap.2014.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Induced Leucine Zipper inhibits apoptosis of cardiomyocytes by doxorubicin

Abstract: Doxorubicin (Dox) is an indispensable chemotherapeutic agent for the treatment of various forms of neoplasia such as lung, breast, ovarian, and bladder cancers. Cardiotoxicity is a major concern for patients receiving Dox therapy. Previous work from our laboratory indicated that glucocorticoids (GCs) alleviate Dox-induced apoptosis in cardiomyocytes. Here we have found Glucocorticoid-Induced Leucine Zipper (GILZ) to be a mediator of GC-induced cytoprotection. GILZ was found to be induced in cardiomyocytes by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…The relationship between GILZ and Bcl-xL was reported previously, and the antiapoptotic function of GILZ is mediated by the upregulation of Bcl-xL. 12,29 In the present study, GILZ overexpression upregulated retinal Bcl-xL, whereas GILZ silencing enhanced the decrease in retinal Bcl-xL at the mRNA and protein levels. These results indicate that the antiapoptotic effects of GILZ in the retina may be mediated by the maintenance of retinal Bcl-xL levels.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The relationship between GILZ and Bcl-xL was reported previously, and the antiapoptotic function of GILZ is mediated by the upregulation of Bcl-xL. 12,29 In the present study, GILZ overexpression upregulated retinal Bcl-xL, whereas GILZ silencing enhanced the decrease in retinal Bcl-xL at the mRNA and protein levels. These results indicate that the antiapoptotic effects of GILZ in the retina may be mediated by the maintenance of retinal Bcl-xL levels.…”
Section: Discussionsupporting
confidence: 80%
“…12 In cardiomyocytes, GILZ overexpression protects cells from apoptosis by upregulating Bcl-xL expression, preventing cytochrome c release from mitochondria and caspase-3 cleavage. 13 Bruscoli et al 14…”
mentioning
confidence: 99%
“…These observation are consistent with those of our recent study , whereby intramyocardial treatment with GILZ-overexpressing mesenchymal stem cells exerted significant cardioprotection. Others (Aguilar et al, 2014) have shown that GILZ overexpression protects against doxorubicin-induced cardiomyopathy, as exemplified by the induction of prosurvival protein Bcl-xL, the prevention of mitochondrial release of cytochrome c, and the cleavage of caspase-3. Similarly, GILZ overexpression protects against endoplasmic reticulum stress-mediated cell death, likely via the stimulation of mitochondrial oxidative phosphorylation (André et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2007 ). As such, GR-target gene GILZ was shown to induce Bcl-xL expression thereby protecting cardiomyocytes for doxorubicin cytotoxicity ( Aguilar et al . 2014 ).…”
Section: Discussionmentioning
confidence: 99%